The Role of Organizational Citizenship Behavior (OCB) in Moderating the Relationship Between Entrepreneurial Leadership, Organizational Climate, and Workload on Employee Performance - Sitepu, Rimenda Aminarosa; Harianto, Eric; Sarwoko, Endi (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2024)
This study aims to review employee performance at a private school in Surabaya by analyzing the influence of entrepreneurial leadership, organizational climate, workload, and OCB on employee performance. We use structural equation modeling (SEM) as the method to study complex relationships between variables. The study seeks to provide in-depth insights into the factors affecting employee performance and assist schools in designing strategies to enhance achievement and competitiveness. The results indicate that entrepreneurial leadership, organizational climate, and workload do not have a significant direct impact on employee performance. However, OCB has a significant effect on performance. Additionally, organizational climate and workload significantly influence OCB, while entrepreneurial leadership does not have a significant effect on OCB. These findings highlight the importance of OCB in improving employee performance, as well as the necessity of creating a conducive organizational climate and effectively managing workload to maximize employee contributions in educational institutions.